IMF Research Bulletin, March 2002. (IMF Research Bulletin; IMF Research Bulletin ;, 2002)
Articles reviewing IMF research on dollarization and on the relationship between macroeconomic policies and income distribution; country/area study: The Euro Area; summaries of Second Annual IMF Research Conference and Investor Relations Seminar; list of external publications of IMF staff; IMF working papers; visiting scholars at the IMF.